ANALYSIS OF THE INFLUENCE OF MARKETING MIX ON THE DECISION TO PURCHASE KEBAGUSAN IV RESIDENCE - Gamal Rahmatullah; Nobelson Nobelson (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
The purpose of this study was to analyze the influence of product, price, location and promotion variables on purchasing decisions at Kebagusan IV Residence. In this study, quantitative methods were used to determine and analyze the effect of product, price, location and promotion on purchasing decisions at Kebagusan IV Residence. This population & sample collection was taken from consumers who bought houses at Kebagusan IV Residence by distributing questionnaires to 35 respondents. Processing and analyzing the collected data, especially by using descriptive analysis techniques and inferential analysis, namely by using the SmartPLS application (V.4.0). The results of this study indicate that (1) Product has a positive and significant effect on purchasing decisions with a path coefficient of 0.512. (2) Price has a negative and significant effect on purchasing decisions with a path coefficient of -0.178. (3) Location has a positive and significant effect on purchasing decisions with a path coefficient of 0.232. (4) Promotion has a positive and significant effect on purchasing decisions with a path coefficient of 0.451. Product, price, location and promotion together influence 0.917 (91.7%) purchasing decisions, while the remaining 0.083 (8.3%) are influenced by other factors outside of the variables of this study such as economic, psychological, family and socio-cultural factors.